The abscisic acid signaling negative regulator OsPP2C68 confers drought and salinity tolerance to rice - Beilei Wang; Yuping Luo; Binxia Zhong; Han Xu; Fengping Wang; Wen Li; Meiqi Lin; Juan Chen; Liangbi Chen; Manzhong Liang; Xiaojun Dai (Scientific Reports)
Abstract Clade A type 2 C protein phosphatases (PP2CAs) are core regulatory factors in the plant abscisic acid (ABA) signaling pathway. They play crucial roles in response to abiotic stress. However, a comprehensive understanding of the functions of individual members of rice PP2CA gene families remains limited. This study investigates the role of OsPP2C68 in response to abiotic stress. Our findings indicated that the OsPP2C68 is highly expressed in the embryo and endosperm, and is subcellular localized in the nucleus. OsPP2C68 knockout mutants reduced seed germination and root and stem lengths under ABA treatment. The mutants also exhibited higher stomatal closure rates, indicating increased sensitivity to ABA. In addition, the OsPP2C68 knockout mutants exhibited altered synthesis of osmolytes and antioxidant enzymes under drought and high salinity stress, along with the differential expression of genes associated with drought and salt stress responses, enhancing rice tolerance to drought and salt. These results collectively identify OsPP2C68 as a negative regulator in the rice ABA signaling pathway. It is responsive to drought and salt stress, and involved in regulating stomatal movement.